Complete sequence of mitochondrial DNA of Gracilaria tenuistipitata var. liui (Rhodophyta) - Xianming Tang; Yue Li; Wei Zhou Chen; Tao Liu; Jing Zhang (Mitochondrial DNA. Part B. Resources, 2018)
Here, the complete Gracilaria tenuistipitata var. liui mitogenome was determined and analyzed. The complete G. tenuistipitata var. liui mitogenome length was 25,879 bp and contained 50 genes including 24 protein-coding, 2 rRNA, and 23 tRNA genes and one unidentified open reading frame (ORF). Of the 24 protein-coding genes, 23 (95.83%) terminated with the stop codon TAA, and one (4.17%) with TAG (rps3 gene). All protein-coding genes in G. tenuistipitata var. liui started with ATG codon. Mitogenome phylogenetic analysis revealed that G. tenuistipitata var. liui firstly clustered together with Gracilaria tenuistipitata. The complete mitogenome sequence would help in understanding Gracilaria evolution.